Platelets (thrombocytes): The other recognized functions - Nikolić Ljubinka I.; Vuković-Suvajdžić Nada D.; Bugarinović Snežana M.; Plećaš Darko V. (Srpsko lekarsko drustvo, 2016)
Introduction: Platelets are smallest blood cells of discoid or round shape and are cytoplasmic fragments of megakaryocytes. Platelets consist of 3 types of granules: alpha granules, dense granules and lysosomes. Granule secretion releases coagulation factors, growth factors, cytokines, and a number of proteolytic enzymes. Platelets contain a number of receptors known as platelet agonists. Basic and most studied role of platelets is in hemostasis process. The aim of this paper is to point on platelet function unrelated to hemostasis. Matherials and methods: Papers on other recognized functions of platelets were searched for in biomedical journals idexed in MEDLINE form 2004 to 2016. Topic: This paper studies less known platelet functions becoming subject of interest with the development of applied science. Platelets participate in inflammation by releasing proinflammatory mediators (CD154, CD40L). Complement activation via Pselectin, platelet-generates immunomodulatory effect. CD40L accelerates releasing RANTES protein leading to intensified activation of T-lymphocytes. During embryonic development, platelets allow blood and lymph vessels separation by activating CLE-2 receptor and ligand PDPN. Platelets alleviate migration and invasiveness of tumor cells, contribute to disease progression and development of metastases. Platelets affect maturation of follicles and oocytes and have important role in embryo implantation process and placentation. Conclusion: Based on these findings, conclusion imposes platelets as not only active participants in the hemostasis process but as having significant role in inflammation, unspecified and specified body defending, tumor biology, embryonic development and in female reproductive system regulation. Numerous roles of platelets open wide range for the new drugs' operation. Their specific characteristic is the basis for the personalized Clinical pharmacology development and possibility of applying specific drug as polyindicative therapeutic agent.